Contrast enhancement of multi-displays using human contrast sensitivity - Majumder, A. (2005 IEEE Computer Society Conference on Computer Vision and Pattern Recognition (CVPR'05), 2005)
Study of contrast sensitivity of the human eye shows that we are more sensitive to brightness differences at low intensity levels than at high intensity levels. We apply this fact effectively to achieve brightness seamless-ness in multi-projector displays. Multi-displays, popularly made of a rectangular array of partially overlapping projectors, show severe spatial variation in brightness. Existing methods achieve brightness uniformity across the display by matching the brightness response of every pixel to the pixel with the most limited contrast leading to severe compression in the contrast of the display. In this paper, we propose a method that allows a constrained variation in brightness guided by the human contrast sensitivity function such that it is imperceptible to the human eye. This achieves a seamless multi-display with a dramatic improvement in the contrast making the display practically usable.